Developing an assessment instrument to measure the minimum competency of high school physics using item response theory - Novika, Resti; Istiyono, Edi; Notiavina, Andriandrainiarimanana Anjamampionona (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The minimum competence of reading literacy and numeracy is a fundamental competency that students must possess to participate in society. The government stipulates a minimum competency assessment as a basic assessment to develop students' self-quality. This research aims to produce a minimum competency assessment instrument (MCA) for high school physics. This research is research and development research. Selection of test subjects using purposive sampling with 321 samples. This research and development resulted in the quality of the MCAPhys instrument in terms of content validity; Aiken's V score was in the valid category. The empirical validity based on item compatibility with the IRT Rasch model and PCM approach proved that 80 items fit the model. Reliability estimation based on Cronbach's Alpha reliability is obtained with very reliable criteria. The item difficulty level is in the range of -3.5 to 2.9. The quality of the developed MCAPhys test instrument meets the eligibility of the test instrument so that it can be used as a reference for teachers making minimum competency assessment instruments and as practice questions by students. This finding is a significant contribution to the development of education, especially related to the provision of an instrument model based on empirical evidence. This test development framework can be adapted to other subjects and added to the study of the validity and reliability of minimum competency assessments.